2009
DOI: 10.1097/jom.0b013e3181a1f5c8
|View full text |Cite
|
Sign up to set email alerts
|

The Direct and Indirect Costs of Employee Depression, Anxiety, and Emotional Disorders—An Employer Case Study

Abstract: The cost burden of depression, anxiety, and emotional disorders is among the greatest of any disease conditions in the workforce. It is worth considering methods for quantifying direct and indirect costs that use administrative data sources given their utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 49 publications
0
12
0
4
Order By: Relevance
“…Previous studies have found higher healthcare costs among migraineurs with comorbid anxiety and/or depression than those without. 12,13 Many of the comorbidities that were more prevalent in the migraine sample have also been found to be associated with increased indirect costs; for example, depression and anxiety, 34,35 osteoarthritis, 36 and inflammatory bowel disease. 37 Another explanation for the lower costs reported in the survey study is that the average hourly wage rate used in that study was lower than that used in this study.…”
Section: Discusssionmentioning
confidence: 98%
“…Previous studies have found higher healthcare costs among migraineurs with comorbid anxiety and/or depression than those without. 12,13 Many of the comorbidities that were more prevalent in the migraine sample have also been found to be associated with increased indirect costs; for example, depression and anxiety, 34,35 osteoarthritis, 36 and inflammatory bowel disease. 37 Another explanation for the lower costs reported in the survey study is that the average hourly wage rate used in that study was lower than that used in this study.…”
Section: Discusssionmentioning
confidence: 98%
“…Depression and/or anxiety diagnoses are associated with at least 50% increased direct health care costs [McLaughlin et al, ]. When estimates include inpatient care, outpatient services, and pharmacy costs, the direct health care costs for employers are nearly nine times higher for employees with depression, anxiety, and/or emotional disorders compared with employees without these diagnoses [Johnston et al, ]. The indirect costs to employers may be even more substantial, due to increased absenteeism, defined as habitual absence from work, and presenteeism, defined as working at lower than normal productivity, associated with poor mental health [Munce et al, ; Kessler et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Struggling at work as well as being absent are parts of the continuum of work disability [23]. This is especially pertinent here, given the recurring nature of CHMCs and associated absences and performance deficits [24], both of which have significant personal, organizational and societal costs [25]. Also, WDP interventions for those two worker groups often share core components, such as psychological support and stress management, relapse prevention strategies, assistance with locating community resources, ergonomic analysis and work accommodations, that aim to help workers function better at work [26].…”
mentioning
confidence: 99%